2021
DOI: 10.1177/01945998211021023
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors and Outcomes of De Novo Sinonasal Squamous Cell Carcinoma: A Systematic Review and Meta‐analysis

Abstract: Objective To review overall survival (OS), recurrence patterns, and prognostic factors of de novo sinonasal squamous cell carcinoma (DN-SCC). Data Sources PubMed, Scopus, OVID Medline, and Cochrane databases from 2006 to December 23, 2020. Review Methods The study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. Articles were required to report either recurrence patterns or survival outcomes of adults with DN-SCC. Case reports, books, reviews, meta-analyses, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 77 publications
1
5
2
Order By: Relevance
“…Similarly, a systematic review of 41 studies reported 55% 5-year OS and 43% recurrence in patients with DN-SCC (6) . The apparent survival and recurrence differences in these reviews provides evidence for DN-SCC and IP-SCC being distinct entities, though survival outcomes between DN-SCC and IP-SCC had not been directly compared through a systematic review and meta-analysis until recently (4,(7)(8)(9)(10)(11)(12)(13)(14) .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Similarly, a systematic review of 41 studies reported 55% 5-year OS and 43% recurrence in patients with DN-SCC (6) . The apparent survival and recurrence differences in these reviews provides evidence for DN-SCC and IP-SCC being distinct entities, though survival outcomes between DN-SCC and IP-SCC had not been directly compared through a systematic review and meta-analysis until recently (4,(7)(8)(9)(10)(11)(12)(13)(14) .…”
Section: Introductionmentioning
confidence: 92%
“…Previously, we have reported survival and recurrence outcomes of both IP-SCC and DN-SCC alone as systematic reviews. The systematic review on DN-SCC included 43 studies and reported aggregate survival and recurrence information (6) . The systematic review on IP-SCC included 28 studies with reporting of similar outcomes measures (5) .…”
Section: Newcastle-ottawamentioning
confidence: 99%
“…Nonetheless, HPV infection appears to play an etiologic role in approximately 25% of SNSCC. It is proposed that HPV‐associated SNSCC confers an improved prognosis 1062,1063 . Similarly, EBV has been detected in SNSCC.…”
Section: Sinonasal Squamous Cell Carcinomamentioning
confidence: 99%
“…Additionally, though cervical lymph node metastasis is uncommon overall for SNSCC, a maxillary site of origin is much more likely to present with nodal metastasis than nasoethmoidal SNSCC. Cervical metastases, when present, confer worse prognosis 231,1063 …”
Section: Sinonasal Squamous Cell Carcinomamentioning
confidence: 99%
See 1 more Smart Citation